Implementasi Teknologi Digital dalam Pendidikan Seni: Studi Kasus di SD Sinar Dharma Jakarta Barat - Chandra, Edy; Setiawan, M Nashir; Mariana, Mariana; Sulystiawati, Dwi; Warjoyo, Jayanto Ginon (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
This Community Service Program (PKM) aims to provide digital drawing visualization training to students of SD Sinar Dharma, West Jakarta. The program is conducted by lecturers and students from the Visual Communication Design Study Program, Faculty of Art and Design, Tarumanagara University (UNTAR). The training utilizes the IBIS Paint application to teach basic digital drawing techniques, coloring, and creating simple illustrations. This activity not only enhances students' technical skills in digital art but also fosters their creativity and imagination. Additionally, the program is expected to nurture students' interest and talent in the arts, providing them with skills relevant to current technological advancements. The outcomes of this activity include a journal manuscript and a mapping concept through a poster submitted as Intellectual Property Rights (HAKI). With an interactive and innovative approach, this activity positively impacts the educational development and creativity of SD Sinar Dharma students.